2007
DOI: 10.1088/1126-6708/2007/08/007
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical thermodynamics of scalar fields

Abstract: We present a systematic semiclassical procedure to compute the partition function for scalar field theories at finite temperature. The central objects in our scheme are the solutions of the classical equations of motion in imaginary time, with spatially independent boundary conditions. Field fluctuations -both field deviations around these classical solutions, and fluctuations of the boundary value of the fields -are resummed in a Gaussian approximation. In our final expression for the partition function, this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…( 9) was done in Ref. [6] as an intermediate step to obtain the pressure in the context of a semiclassical approximation. There, it was shown that this quantity can be expressed, for constant φ 0 , in terms of solutions of the equation for small field perturbations propagating on top of the classical solution φ c 1 2…”
Section: The One-loop Effective Potential In Betmentioning
confidence: 99%
See 2 more Smart Citations
“…( 9) was done in Ref. [6] as an intermediate step to obtain the pressure in the context of a semiclassical approximation. There, it was shown that this quantity can be expressed, for constant φ 0 , in terms of solutions of the equation for small field perturbations propagating on top of the classical solution φ c 1 2…”
Section: The One-loop Effective Potential In Betmentioning
confidence: 99%
“…II, we revisit the usual prescription to obtain the effective action and the effective potential in the functional integral formalism; using the results of Ref. [6], we write the effective potential in terms of the solution of a certain differential equation. In Sec.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this caveat in mind, we will continue to refer to x 0 as a mode of x. 3 With the normalization factor used in Eq. ͑25͒, one has the property: V eff ͑x 0 ͒ → V͑x 0 ͒ when T → ϱ, as follows from Eq.…”
Section: High-temperature Expansionmentioning
confidence: 99%
“…In order to integrate (3) over boundary values in the neighborhood of ϕ s (x), we can use the techniques of Ref. [9], which incorporate fluctuations of boundary conditions. We write the boundary field as ϕ(x) = ϕ s (x)+ξ(x), and expand the action up to quadratic order in ξ.…”
Section: Introductionmentioning
confidence: 99%